Job Maturity in Improving Teacher Performance at Public Vocational High School 1 Ketapang - Vita Kusnul Fauzi; Wahyudi Wahyudi; Sukmawati Sukmawati (Ridwan Institute, 2022)
This study aims to determine: 1) Want to know and analyze the performance of masters at Public Vocational School 1 Ketapang in carrying out their duties as masters; 2) Want to know and analyze what work maturity can improve master's performance at Public Vocational School 1 Ketapang; 3) Want to know and analyze the efforts made by the master of Public Vocational School 1 Ketapang in improving performance as a master. Measurement in this study using qualitative methods. The results and analysis show that: 1) Based on the results of observations, interviews, and documentation studies conducted by researchers on informants (research subjects), namely the masters of State Vocational High Schools, it shows that the masters have met several assessment indicators for each aspect. 2) Based on the results of the research on the masters of Public Vocational School 1 Ketapang above, it shows that the performance of the masters of Public Vocational School 1 Ketapang in terms of professional competence is in the fairly good category. This is because the master has fulfilled several assessment indicators in mastering the material, structure, concept, and scientific mindset that supports the subject, developing creatively guided subject matter, continuing professional development by taking reflective actions and utilizing information and communication technology to develop themselves. 3) Efforts made by the master of Public Vocational School 1 Ketapang in improving performance as a master, from the learning outcomes, namely by carrying out their duties as well as possible and continuing to improve pedagogic and professional competencies.